Effect of Integrated Capacity-Building Interventions on Malaria Case Management by Health Professionals in Uganda: A Mixed Design Study with Pre/Post and Cluster Randomized Trial Components - Kayitale Mbonye, Martin; Burnett, Sarah M.; Burua, Aldomoro; Colebunders, Robert; Crozier, Ian; Kinoti, Stephen N.; Ronald, Allan; Naikoba, Sarah; Rubashembusya, Timothy; Van geertruyden, Jean-Pierre; Willis, Kelly S.; Weaver, Marcia R. (PloS one, 2014)
The Integrated Infectious Diseases Capacity Building Evaluation (IDCAP) designed two interventions: Integrated Management of Infectious Disease (IMID) training program and On-Site Support (OSS). We evaluated their effects on 23 facility performance indicators, including malaria case management. Methodology: IMID, a three-week training with two follow-up booster courses, was for two mid- level practitioners, primarily clinical officers and registered nurses, from 36 primary care facilities. OSS was two days of training and continuous quality improvement activities for nine months at 18 facilities, to which all health workers were invited to participate. Facilities were randomized as clusters 1:1 to parallel OSS ‘‘arm A’’ or control ‘‘arm B’’. Outpatient data on four malaria case management indicators were collected for 14 months. Analysis compared changes before and during the interventions within arms (relative risk = RR). The effect of OSS was measured with the difference in changes across arms (ratio of RR = RRR). Findings: The proportion of patients with suspected malaria for whom a diagnostic test result for malaria was recorded decreased in arm B (adjusted RR (aRR) = 0.97; 99%CI: 0.82,1.14) during IMID, but increased 25% in arm A (aRR = 1.25; 99%CI:0.94, 1.65) during IMID and OSS relative to baseline; (aRRR = 1.28; 99%CI:0.93, 1.78). The estimated proportion of patients that received an appropriate antimalarial among those prescribed any antimalarial increased in arm B (aRR = 1.09; 99%CI: 0.87, 1.36) and arm A (aRR = 1.50; 99%CI: 1.04, 2.17); (aRRR = 1.38; 99%CI: 0.89, 2.13). The proportion of patients with a negative diagnostic test result for malaria prescribed an antimalarial decreased in arm B (aRR = 0.96; 99%CI: 0.84, 1.10) and arm A (aRR = 0.67; 99%CI: 0.46, 0.97); (aRRR = 0.70; 99%CI: 0.48, 1.00). The proportion of patients with a positive diagnostic test result for malaria prescribed an antibiotic did not change significantly in either arm.
Keywords: Capacity-Building; Malaria Case Management; Health Professionals; Cluster Randomized Trial Components